Free trade or fair trade? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The 'Partners for Development' Summit meeting held in Lyon (France), from 9 to 12 December 1998, was convened by the United Nations Conference on Trade and Development (UNCTAD)